8.3x+5=9.7x-1

Simple and best practice solution for 8.3x+5=9.7x-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8.3x+5=9.7x-1 equation:


Simplifying
8.3x + 5 = 9.7x + -1

Reorder the terms:
5 + 8.3x = 9.7x + -1

Reorder the terms:
5 + 8.3x = -1 + 9.7x

Solving
5 + 8.3x = -1 + 9.7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9.7x' to each side of the equation.
5 + 8.3x + -9.7x = -1 + 9.7x + -9.7x

Combine like terms: 8.3x + -9.7x = -1.4x
5 + -1.4x = -1 + 9.7x + -9.7x

Combine like terms: 9.7x + -9.7x = 0.0
5 + -1.4x = -1 + 0.0
5 + -1.4x = -1

Add '-5' to each side of the equation.
5 + -5 + -1.4x = -1 + -5

Combine like terms: 5 + -5 = 0
0 + -1.4x = -1 + -5
-1.4x = -1 + -5

Combine like terms: -1 + -5 = -6
-1.4x = -6

Divide each side by '-1.4'.
x = 4.285714286

Simplifying
x = 4.285714286

See similar equations:

| 121x^2-324= | | -9/-3*2/-5*8 | | x+x-28=152 | | -5/6t=15 | | y=2x^2+12x-39 | | 9a^3-5a^3= | | (x^4-25)(x^2-1)=0 | | 0.05*(x^90)=5 | | 12x+3=18x-3 | | 27w/-12w | | 4(m+4)+8(-12m+11)=m-8+8m+11 | | 8(w-84)=88 | | 81=-9(j+87) | | 5(p-65)=85 | | -7(t-9)+2t=-8+t | | 27-m=8 | | 2x/4-1/4=x/3-7/3 | | 4a-11=9+3a | | 5(-6+1)-4n=-5+2n | | 24=-3(t+-24) | | 2(n-52)-22=2 | | 2(t-64)=56 | | 67-z=40 | | 2(s+1)=10 | | 4(s-90)=-50 | | (5x-6)(x^2-4x-1)= | | (4x^2)-47+70=0 | | M-52=27 | | 3(v+2)=12 | | 3(b+1)+1=10 | | 3(z+-15)=-60 | | 25-w=46 |

Equations solver categories